Reshaping Agriculture and Development in Southeast Asia: An Experts Consultation Forum - Southeast Asian Regional Center for Graduate Study and Research in Agriculture (2019)
The report documents the experts consultation forum on Reshaping Agriculture and Development in Southeast Asia held on 2 August 2018 at the SEARCA Headquarters, Laguna, Philippines. The forum aimed to distill from current developments and emerging scenarios the opportunities and challenges for direction setting and strategizing toward an integrated AD agenda in Southeast Asia to proactively address these rapid changes. Specifically, the regional experts consultation forum aimed for the following: Analyze opportunities and challenges for agriculture and development in the Southeast Asian region in the next 5–10 years; Calibrate the thrusts and themes where regional and national institutions and networks in Southeast Asia may collaborate and complement one another along the current and projected gaps/needs of the region in AD; and Recommend directions and innovative approaches in the pursuit of shared regional mandates, goals, and programs.